Rationed Fertility: Treatment Effect Heterogeneity in the Child Quantity-Quality Trade-Off - Guo, Rufei; Yi, Junjian; Zhang, Junsen; Zhang, Ning (Journal of Political Economy, 2025)
We develop a generalized theory of rationed fertility to analyze treatment effect heterogeneity in the child quantity-quality trade-off. An exogenous increase in fertility can be either desired or undesired. We derive a positive rationing income effect on child quality for desired fertility increases but a negative rationing income effect for undesired fertility increases. We propose an econometric framework to identify treatment effects of desired and undesired fertility increases and estimate a structural model to gauge the quantitative importance of the novel rationing income effect. Our study highlights the importance of distinguishing between desired and undesired changes when evaluating social programs.